2011
DOI: 10.1159/000327946
|View full text |Cite
|
Sign up to set email alerts
|

FLNA and PGK1 are Two Potential Markers for Progression in Hepatocellular Carcinoma

Abstract: Background/Aims: Hepatocellular carcinoma (HCC) is one of the most deadly diseases; metastasis and recurrence are the most important factors that affect the therapy of HCC chronically. Until now, the prognosis for the metastasis of HCC had not improved. Recently, several proteins that are related to metastasis and invasion of HCC were identified, but the effective markers still remain to be elucidated. Methods: In this study, comparative proteomics was used to study the differentially expressed proteins in two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
59
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(63 citation statements)
references
References 40 publications
3
59
1
Order By: Relevance
“…Notably, the present study identified differential expression of FLNA and FLNB in the cytoplasmic proteins, which is consistent with findings reported by Ai et al (8). Aside from the two proteins in the cytoplasm, nucleolin was the only differentially expressed protein among the proteins isolated from the nucleus, and it provided a novel candidate for the diagnosis and treatment of HCC.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Notably, the present study identified differential expression of FLNA and FLNB in the cytoplasmic proteins, which is consistent with findings reported by Ai et al (8). Aside from the two proteins in the cytoplasm, nucleolin was the only differentially expressed protein among the proteins isolated from the nucleus, and it provided a novel candidate for the diagnosis and treatment of HCC.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, the lack of good early diagnostic markers has rendered this disease a major challenge. Previous studies have investigated certain molecules associated with the progression and metastasis of HCC, including transforming growth factor-β1 (TGFβ) (19), insulin-like growth factor II (IGF-II) (20), the human cervical cancer oncogene (HCCR) (21), FLNA and PGK1 (8). However, these biomarkers are not adequately specific and sensitive.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[21][22][23] Interestingly, the high expression of PGK-1 is significantly correlated with tumor progression, metastasis and multidrug resistance in various cancers. 21,22,[24][25][26] It has also been reported that the expression of PGK-1 in PCa cells could induce bone formation 27 and that cancer-associated fibroblasts, which showed strong expression of PGK-1, could promote PCa growth, 28 suggesting that PGK-1 plays important roles in PCa development, progression and bone metastasis. In addition, both PGK-1 and AR genes are located within Xqll-Xql3 region and PGK-1 short tandem repeat polymorphism linkage to AR in the expression of miR-29a has been found to be correlated with short survival, more invasive phenotype, and early recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…Although downregulation of FLNA expression increases the invasiveness of human breast cancer cells (Cunningham et al, 1992;Xu et al, 2010), a positive effect of FLNA on cell migration has also been reported (Castoria et al, 2011;Cunningham et al, 1992). FLNA expression levels in tumors and plasma of patients with breast and primary brain tumors increase with tumor malignancy (Ai et al, 2011;Alper et al, 2009;Bedolla et al, 2009). Finally, a most recent study has demonstrated that FLNA knockout restrains development of KRas induced lung tumors in mice (Nallapalli et al, 2012).…”
Section: Introductionmentioning
confidence: 98%